Scanning electron microscopy, biochemical and enzymatic studies to evaluate hydro-priming and cold plasma treatment effects on the germination of Salvia leriifolia Benth. seeds - Ghodsimaab, Seyedeh Parisa; Makarian, Hassan; Ghasimi Hagh, Ziba; Gholipoor, Manoochehr (Frontiers in Plant Science, 2023)
Finding a suitable method to increase the seed germination of medicinal plants is a critical key to saving them. The effect of cold plasma (CP) (surface power densities, including 80 and 100 W in exposure time 0, 120, 180, and 240 s) incorporated with hydro-prime (24 and 2 h on seeds with normal and uncovered, respectively) to enhance seed germination of Salvia leriifolia Benth, as a native endangered Iranian medicinal plant, were evaluated in this study. Scanning electron microscopy (SEM) images, identified destroyed mesh-like structures in hydro-primed and uncovered seeds were more than the normal and dry seeds. In comparison to the control, and other treatments, employing 100 W of CP for 240s produced the maximum germination percentage and rate as well as seedling vigour I and II in hydro-primed and uncovered seeds. α-amylase activity increased by increasing the power and exposure times of CP. Un-covering and hydro-priming of S. leriifolia seeds resulted in increased enzyme activity. Malondialdehyde (MDA) and hydrogen peroxide (H2O2) contents are enhanced by increasing the power and exposure time of CP, especially in uncovered and hydro-primed seeds. The activity of antioxidant enzymes, including catalase (CAT) and superoxide dismutase (SOD), was in accordance with changes in MDA and H2O2 contents. Finally, direct contact of CP with uncovered seeds in a short exposure time can improve the germination of these via a microscopic etching and activation of enzymes.